HOUSEHOLD COPING STRATEGIES FOR DOMESTIC ENERGY PRICE CHANGES IN NORTHEASTERN NIGERIA (2011)
In Nigeria, high cost of Domestic Energy (DE) has put untold hardship on households. Coping strategy is therefore imperative to meet household domestic cooking and heating needs. Investigating evolving strategies would better inform DE experts and policy makers. This study was therefore designed to investigate strategies devised by households in Northeastern Nigeria for coping with the escalating prices of DE. The domestic energy types considered in the study include Liquefied Natural Gas (LNG), Liquefied Petroleum Gas (LPG), kerosene, electricity, coal, solar energy, animal dung, agricultural residues and wood energy. Other potential energy sources in Nigeria include volcanic and refuse fuel, tidal and wind energy and geothermal, which are yet to be exploited. Borno, Gombe and Taraba states were selected for the study through stratified random sampling that gave due cognisance to representative vegetation zone of Northeastern Nigeria. Twenty percent of the total number of Local Government Areas (LGAs) in Borno (27), Gombe (11) and Taraba (16) states respectively were randomly selected comprising urban, semi-urban and rural LGAs. Two wards were selected from each LGA making a total of 20 wards for the study. Four sets of questionnaire were administered, each on 25 household heads, six DE marketers, two heads of government forestry agencies and three community leaders in each ward. Information elicited focussed on DE price changes, factors determining choice of DE and coping strategies evolved by households between 2006 and 2007. Descriptive statistics, Chi-Square, Logistic regression and correlation tests were used to analyse the data at p≤0.05. Eighty two percent of the household heads were male, 81.7% were married, and 33.2% had secondary school education while 54.2% were farmers. The mean age of household heads was 42.0 ± 3.0 years while the mean monthly income was ₦11,228 ± 2,345:00. Fuelwood, (90.0%), kerosene, (74.4%), charcoal, (83.2%), electricity (49.2%) and, cooking gas (13.6%) were DE severally identifiable by community leaders. Factors determining choice of DE among households were cost (94.8%), regular availability (94.4%), and ease of use (81.8%). UNIVERSITY OF IBADAN LIBRARY iii Mean monthly expenditure on DE in the urban areas was N12,300.00 ± 1000.00 compared to N4,345.00 ± 525.00 for those in semi-urban and N932.00 ± 178.00 in the rural areas. Fuelwood was the most popular DE (81.3%), followed by electricity (14.0%) and kerosene 5.7%. Findings from DE marketers indicated that kerosene had the highest price increase from N17.00/litre to N53.6/litre (215.5%), followed by fuelwood N20.00/33% of a cord to N45.3/33% of a cord (126.7%), charcoal N200.0/16kg to N412.0/16kg (106%) and cooking gas N7,500.0/12kg cylinder to N13,350/12.5kg cylinder (78%) between 1999 to 2005. The favoured household coping strategies on DE were reduction in the rate of DE use (40.8%), cutting expenditure on other household needs (21.2%), and suspension of capital projects (13.1%). Substituting of fossil-based energy with biomass (13.1%) and keeping of domestic animals (11.8%). Adoption of coping strategies varies significantly among households’ characteristics. Gender and settlement type significantly influenced adoption of coping strategies. The price sensitive to adjust to price of fuelwood from that of kerosene are noticed in the semi-urban (r = 0.9729) and urban (r= 0.9623) areas of guinea savannah, urban areas of Sudan (r = 0.9616) followed by rural areas of guinea savannah (r = 0.9166), while the least price sensitive to adjust to prices of fuelwood from that of Kerosene are in the semi-urban (r = 0.7893) and urban (r = 0.7873) of Sahel zone areas and rural (r = 0.6670) areas of Sudan. Ninety three percent of heads of government forestry agencies attributed the upsurge in the use of fuelwood by households to high cost of fossil-based DE and viewed it as a threat to forest conservation. Fuelwood is the most popular alternative DE in the Northeastern Nigeria. This could have potential negative impact on the fragile savannah ecosystem. Increased efforts at afforestation will compliment fuelwood supply in the region and help in stabilizing the ecosystem. Key words: Domestic energy, Energy Prices, Coping strategies, Households, Northeastern Nigeria Word count: 490